2019
DOI: 10.1103/physrevmaterials.3.065005
|View full text |Cite
|
Sign up to set email alerts
|

Quantum size stabilization of Ge3Pt nanofilms on Ge(001)

Abstract: The electronic and structural properties of a Ge-Pt alloy film on Ge(001) were studied with low-energy electron microscopy. Well above 1000 K, a bulklike eutectic film forms, followed by the emergence of an ordered Ge 3 Pt alloy upon solidification, which sets in at 1004 K. This eight-layers-thick Ge 3 Pt phase is remarkably robust as it is stabilized by quantum size effects. Further cooling results in the evolution of ultrathin Pt-induced nanowires around 650 K. The process is reversible upon temperature vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(102 citation statements)
references
References 29 publications
(49 reference statements)
5
95
1
1
Order By: Relevance
“…Since mounds partially block P 2p signals, and the only atoms present on the surface in significant amounts are In and P (from survey XPS, see Figure S2), mounds can only be attributed to In, in the form of ultrathin In layers covering the InP surface as shown in the schematic cross-sectional drawing in Figure 3d. It is noteworthy to mention that the LEEM III system is capable of selected-area low-energy electron diffraction (μLEED) which allows studies of nanoscale films on crystalline substrates, 28 but our previous investigation of similar In mounds on InP(100) showed that μLEED patterns taken with apertures right on the mounds and on areas well away from the mounds do not yield clear differences. 12 The mounds can be considered 2D islands, but they are not generally observed, particularly at high temperatures.…”
Section: N-typementioning
confidence: 99%
“…Since mounds partially block P 2p signals, and the only atoms present on the surface in significant amounts are In and P (from survey XPS, see Figure S2), mounds can only be attributed to In, in the form of ultrathin In layers covering the InP surface as shown in the schematic cross-sectional drawing in Figure 3d. It is noteworthy to mention that the LEEM III system is capable of selected-area low-energy electron diffraction (μLEED) which allows studies of nanoscale films on crystalline substrates, 28 but our previous investigation of similar In mounds on InP(100) showed that μLEED patterns taken with apertures right on the mounds and on areas well away from the mounds do not yield clear differences. 12 The mounds can be considered 2D islands, but they are not generally observed, particularly at high temperatures.…”
Section: N-typementioning
confidence: 99%
“…and applications [1][2][3]. Their unique structures and properties, originating mainly from the quantum size effect, provide an opportunity to explore new phenomena [4][5][6]. On the other hand, 2D materials open up access to new optoelectronic and electronic devices because the carriers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, SAMs are prone to electron-induced damage [1]. Therefore, we alternatively looked at the Bi-modified Ni (111) surface. Bi deposition on the Ni (111) and Cu (111) surfaces has already shown to lead to a variety of dynamic processes [2][3][4][5][6][7].…”
Section: Research Scopementioning
confidence: 99%
“…Therefore, we alternatively looked at the Bi-modified Ni (111) surface. Bi deposition on the Ni (111) and Cu (111) surfaces has already shown to lead to a variety of dynamic processes [2][3][4][5][6][7]. Therefore, the Bi/Ni system was a perfect playground for our study, with the added value that we can further expand our knowledge of its surface phase diagram.…”
Section: Research Scopementioning
confidence: 99%
See 1 more Smart Citation